2010
DOI: 10.4314/sajas.v40i2.57276
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a direct fed microbial (<i>Megasphaera elsdenii</i>) on the productivity and health of Holstein cows

Abstract: ________________________________________________________________________________ AbstractSixty high-producing multiparous Holstein cows were used in a randomized complete block design experiment to determine the effect of a direct-fed microbial (DFM), Megasphaera elsdenii NCIMB 41125 (Me), on dairy cattle productivity and health. The cows received one of two experimental diets (total mixed rations (TMR)) from calving until 60 days post partum. Two experimental diets were formulated, namely a low concentrate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 30 publications
4
19
1
Order By: Relevance
“…In the study by Wallace et al [44] in beef cattle, although not reported in the paper itself, the abundance of M. elsdenii was 13-fold higher in the low-methane steers, thus entirely consistent with the results of Shabat et al [46]. M. elsdenii has been trialled with some success as a probiotic for ruminants on the grounds of its pH-stabilizing properties [52, 53]. Thus, thanks to these studies, a picture is emerging whereby it can be seen that differences in the abundance of H 2 -producing bacteria, non-H 2 -producing bacteria and H 2 utilisers, together with the abundance of pH-stabilizing bacteria, affect the quantity of methane that a ruminant animal produces and its feed efficiency.
Fig.
…”
Section: Reviewsupporting
confidence: 62%
“…In the study by Wallace et al [44] in beef cattle, although not reported in the paper itself, the abundance of M. elsdenii was 13-fold higher in the low-methane steers, thus entirely consistent with the results of Shabat et al [46]. M. elsdenii has been trialled with some success as a probiotic for ruminants on the grounds of its pH-stabilizing properties [52, 53]. Thus, thanks to these studies, a picture is emerging whereby it can be seen that differences in the abundance of H 2 -producing bacteria, non-H 2 -producing bacteria and H 2 utilisers, together with the abundance of pH-stabilizing bacteria, affect the quantity of methane that a ruminant animal produces and its feed efficiency.
Fig.
…”
Section: Reviewsupporting
confidence: 62%
“…This is in contrast to the results of Aikman et al (2009) who found that milk fat and protein were reduced by Me in high-producing cows on both their standard and high-energy diets. Hagg et al (2010) on the other hand found no significant effect of Me on milk composition. These variable responses in milk composition are probably associated with differences in dietary composition and feed processing: the primary energy source in the present trial was steam-flaked sorghum and maize meal, whereas it was wheat and barley in the trial of Aikman et al (2009) and maize meal only in the trial of Hagg et al (2010).…”
mentioning
confidence: 70%
“…Hagg et al (2010) on the other hand found no significant effect of Me on milk composition. These variable responses in milk composition are probably associated with differences in dietary composition and feed processing: the primary energy source in the present trial was steam-flaked sorghum and maize meal, whereas it was wheat and barley in the trial of Aikman et al (2009) and maize meal only in the trial of Hagg et al (2010). It is well-established that these sources differ in ruminal fermentation rate, and consequently in ruminal passage rate (NRC, 2001).…”
mentioning
confidence: 70%
“…Several reports have described experiments in which M. elsdenii was deliberately dosed into the rumen to gauge its effects on ruminal chemistry (pH and organic acid concentrations) and animal performance. These studies have yielded contradictory results (Klieve et al, 2003;Hagg et al, 2010;Meissner et al, 2010;Aikman et al, 2011;Henning et al, 2011); in general, treatment effects on both ruminal pH and milk production and composition have been minimal or absent. But in only one of these studies (Klieve et al, 2003) were any population assessments made to determine whether or not the dosed strain persisted in the rumen, which is a key consideration given the well-known difficulty of establishing exogenously added strains in a well-adapted animal (Weimer, 1998).…”
Section: Introductionmentioning
confidence: 85%